Variable delay-to-signal: a fast paradigm for assessment of aspects of impulsivity in rats - Leite-Almeida, Hugo; Melo, António; Pêgo, José M.; Bernardo, Sara; Milhazes, Nuno; Borges, Fernanda; Sousa, Nuno; Almeida, Armando; Cerqueira, João J. (Frontiers in Behavioral Neuroscience, 2013)
Testing impulsive behavior in rodents is challenging and labor-intensive. We developed a new behavioral paradigm – the Variable Delay-to-Signal (VDS) test – that provides rapid and simultaneous assessment of response and decision impulsivity in rodents. Presentation of a light at variable delays signals the permission for action (nose poke) contingent with a reward. Two blocks of 25 trials at 3s delay flank a block of 70 trials in which light is presented with randomly selected 6s or 12s delays. Exposure to such large delays boosts the rate of premature responses when the delay drops to 3s in the final block, an effect that is blunted by an acute methamphetamine challenge and that correlates with the delay-discounting paradigm (choice impulsivity). Finally, as expected, treatment with the NMDA antagonist MK-801 caused a generalized response increase in all VDS blocks. The pharmacological validation, particularly with methamphetamine which has a well established dual effect on response and decision impulsivity, and the correlations between the impulsive behavior in the delay-discounting and VDS paradigms, suggests that the later is able to provide, in a single session, a multi-dimensional assessment of impulsive behavior.